Registration of 'GA06343‐13E2 (TX‐EL2)' soft red winter wheat. Issue 1 (2nd February 2021) - Ibrahim, Amir M. H.; Sutton, Russell; Johnson, Jerry W.; Mergoum, Mohamed; Simoneaux, Bryan; Harrison, Stephen A.; Murphy, J. Paul; Mason, R. Esten; Babar, Md A.; Neely, Clark; Opeña, Geraldine; Jin, Yue; et al.
Abstract: 'GA06343‐13E2 (TX‐EL2)' (Reg. no. CV‐1172, PI 695071), a medium‐height, medium‐maturing soft red winter wheat ( Triticum aestivum L.) (SRWW), was jointly released by Texas A&M AgriLife Research and the University of Georgia Agricultural Experiment Station in 2019. GA06343‐13E2 (TX‐EL2) was released based on merits of its wide area of adaptation and above‐average grain yield in Texas in particular and the Gulf Atlantic SRWW growing areas in general, in addition to average grain volume weight, good leaf rust and stripe rust resistance, and good end‐use quality characteristics. GA06343‐13E2 (TX‐EL2) was derived from the cross GA011638‐G1/GA961592‐8//GA991336‐47 made at the University of Georgia. The pedigree of GA011638‐G1 is GA01034 ('AGS 2000'*3/96667)/AGS 2000. The pedigrees of GA961592‐8 and GA991336‐47 are GA951329 (GA88129‐32‐3‐5/GA87467‐14‐1‐14‐1)/GA88127‐1‐3‐3 and GA92432‐21‐5‐2/GA981622 [AGS 2000/Pioneer '26R61' (XW663)], respectively. Authorized seed classes of GA06343‐13E2 (TX‐EL2) in the United States will be breeder, foundation, registered, and certified. We will submit GA06343‐13E2 (TX‐EL2) for U.S. Plant Variety Protection with the certification option.